Branched-chain fatty acids from goat milk alleviate ulcerative colitis via the TLR4/NF-κB/NLRP3 pathway - Jiaxin Zhang; Jinjing Zhong; Zhengying Cui; Yu Shen; Yaping Zheng; Yu Zhang; Chaoxin Man; Yanmei Hou; Qianyu Zhao; Yujun Jiang (Food Science and Human Wellness)
Branched-chain fatty acids (BCFAs) are new bioactive fatty acids with anti-inflammatory properties. However, the role of BCFAs in alleviating ulcerative colitis has not been clarified. Herein, we evaluated the protective effect of BCFAs from goat milk in mice with colitis induced using dextran sodium sulfate (DSS) and explored the corresponding mechanism. These results show that BCFAs extracted from goat milk can significantly alleviate weight loss in mice, and reduce the disease activity index and the activity of myeloperoxidase while increasing the content of antioxidant enzymes in colon tissue and reducing the oxidation stress response. These data also show that BCFAs can down-regulate the gene and protein expression of the toll-like receptor 4 (TLR4)/ nuclear factor κB p65 (NF-κB p65)/NOD-like receptor thermal protein domain associated protein 3 (NLRP3) signaling pathway, and at the same time significantly reduce the expression of pro-inflammatory factors tumor necrosis factor α (TNF-α), interleukin 1β (IL-1β), and IL-18 in colon tissue, and significantly increase the expression of the anti-inflammatory factor IL-10. In conclusion, these results demonstrated that BCFAs in goat milk exerted effects on colitis-related inflammatory cytokines and inhibited inflammation by inducing the TLR4/NF-κB/NLRP3 pathway to alleviate DSS-induced ulcerative colitis. This study provides evidence for the potential of BCFAs as bioactive fatty acids in food products and to ameliorate ulcerative colitis development in mice.